A Novel and Efficient Method for Bacteria Genome Editing Employing both CRISPR/Cas9 and an Antibiotic Resistance Cassette - Zhang, Hong; Cheng, Qiu-Xiang; Liu, Ai-Min; Zhao, Guo-Ping; Wang, Jin (Frontiers in Microbiology, 2017)
As Cas9-mediated cleavage requires both protospacer and protospacer adjacent motif (PAM) sequences, it is impossible to employ the CRISPR/Cas9 system to directly edit genomic sites without available PAM sequences nearby. Here, we optimized the CRISPR/Cas9 system and developed an innovative two-step strategy for efficient genome editing of any sites, which did not rely on the availability of PAM sequences. An antibiotic resistance cassette was employed as both a positive and a negative selection marker. By integrating the optimized two-plasmid CRISPR/Cas system and donor DNA, we achieved gene insertion and point mutation with high efficiency in Escherichia coli, and importantly, obtained clean mutants with no other unwanted mutations. Moreover, genome editing of essential genes was successfully achieved using this approach with a few modifications. Therefore, our newly-developed method is PAM-independent and can be used to edit any genomic loci, and we hope this method can also be used for efficient genome editing in other organisms.